POLA KONSUMSI PANGAN RUMAH TANGGA PETANI HUTAN KEMASYARAKATAN DI KABUPATEN LAMPUNG BARAT - Asih Sulistyorini Uly Damora; Faisal Anwar; Yayat Heryatno (Food and Nutrition Society of Indonesia, 2008)
The aims of research were to 1) identify economic and social characteristic of HKm farmer household 2) analyze food consumption pattern of HKm farmer household 3) analyze requirement of food of HKm farmer household 4) analyze factors influencing level of energy and protein consumption sufficiency of HKm farmer household. Design research is cross-sectional study with the sampel size 90 selected by stratified random sampling. Foods consumed are rice, cassava, salted food, tempe, spinach and banana. Consumption of energy was 2 020 kcal per capita per day and consumption of protein equal to 47.9 gram per capita per day. Level of household energy consumption sufficiency is 84.4% as good and protein consumption sufficiency 46.6% as good. Energy consumption sufficiency was influenced by the household size and household expenditure of food, while level of protein consumption sufficiency was influenced by household expenditure of food.